Greece in the European Union - Dimitrakopoulos, Dionyssis G., 1969-; Passas, Argyrēs (Europe and the nation state ;, 2004)
"Greece in the European Union describes Greece's evolution as a Member State, identifying and analysing the dynamics of its involvement in the EU policy process from the perspective of public policy." "This book argues that, although the widely held belief that Greece is a laggard in a number of policy areas is not inaccurate, the pattern of Greek membership of the EU is much more complex, not least because it contains success stories. It will be interest to students and researchers of the European Union, public policy and Greek politics."--Jacket